Towards the Application of Inquiry Learning Approach in Classroom: Students Exploration of Changes in Understanding Meaningful Mathematical Concepts - Nazirah, Filzah; Nuraina, Nuraina; Herizal, Herizal; Mursalin, Mursalin (International Journal for Educational and Vocational Studies, 2021)
This study was intended to investigate the influence of inquiry learning approach assisted with square word media toward students’ mathematical understanding ability in learning mathematics. This study was conducted through quantitative research procedures namely quasi-experimental design. The populations were all students of class X at MAS Syamsuddhuha. The samples were 25 students of class X MIA 1 and 25 students of class X MIA 2, selected by purposive sampling. The nonequivalent posttest-only control group design was used. The data were obtained from the post-test results of the students’ mathematical understanding; they were analyzed by using SPSS 18 software. Since the data was not normal, the non-parametric Mann-Whitney test was applied. The findings of this study showed that the significant value of the test was 0,000 and it was less than 0.05 allowed the H0 rejected. It can be concluded that there was an influence of inquiry learning approach assisted by word square media on students' mathematical understanding ability, which was done in the study of trigonometry II for class X at MAS Syamsuddhuha. Hence, mathematical understanding ability is a crucial aspect in solving mathematical problems which can be measured by applying inquiry learning approach in classroom.